Uma barreira à entrada não tão inocente - Shalders, Felipe Leon Peres Camargo (2012)
In oligopoly theories based on Nash Equilibrium and related concepts, free entry is associated with the coexistence of more than one rm. On the other hand, in the monopoly literature some reasons are identi ed as possible explanations to the permanence of a single pro table rm in the market, but usually do not rely on Nash Equilibrium concept. Here, we provide examples in a game-theoretical approach where randomization between monopoly prices is a new possible explanation for a pro table monopoly with free entry. We construct models where, due to the multidimensionality of goods and heterogeneity of consumers, more than one monopoly price arise, allowing randomization in equilibrium.